BIAYA POLUSI UDARA YANG TIMBUL AKIBAT BERTAMBAHNYA VOLUME KENDARAAN DI KOTA BANDA ACEH - Muamar Ilyas; Muhammad Ilhamsyah Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract Air pollution has become one of the global environmental problems of global concern (Mulyadi, 2015). A survey conducted by the World Health Organization - WHO (2002) in 1,600 cities in 91 countries in the world shows that almost 90 percent of people in urban centers breathe unhealthy air. This study aims to analyze the cost of air pollution arising from the increase in the volume of motor vehicles. The population in this study were all sufferers of diseases caused by air pollution in Banda Aceh City in 2018-2019. While the research sample was carried out using a purposive sampling technique, where the sample taken was limited to only 50 sufferers of air pollution-related illnesses in Banda Aceh City in 2018-2019. The results showed that the average total costs incurred by asthmatics was Rp. 5,500,000 with details of the hospitalization fee of Rp. 2,600,000 and outpatient fees of 2,900,000. The total average cost incurred by sufferers of ARI is Rp. 6,500,000 with details of the hospitalization fee of Rp. 3,100,000 and outpatient costs 3,400,000. ARI sufferers in Banda Aceh City in 2017 reached 7,515 inhabitants. If all ISPA sufferers choose to undergo hospitalization, the gross costs to be incurred reach Rp. 48.847.500.000.Keywords: Cost of air pollution, volume of motor vehicles, air pollution